2016 IEEE Electrical Insulation Conference (EIC) 2016
DOI: 10.1109/eic.2016.7548632
|View full text |Cite
|
Sign up to set email alerts
|

The effect of composition and processing on electric characteristics of XLPE in HVDC cable applications

Abstract: -Polyethylene exhibits many key characteristics including low dielectric loss, high breakdown strength and good processability. Most modern extruded high voltage cables employ cross-linked polyethylene (XLPE) as the insulation material. The main advantage of XLPE is its excellent thermo-mechanical properties; it is relatively cheap and has low dielectric loss and low conductivity making it an ideal material for this application. Crosslinking enhances a number of thermo-mechanical properties such as deformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…It was found that a soaking period of at least 24 hr was needed to ensure the presence of DCP throughout the pellets (see Supplemental Figure 2). The soaked LDPE pellets were placed between two Teflon sheets and compressed at 17.24 MPa (2,500 psi) at 180 C for 12 min, within the typical cross-linking temperature range of 160-220 C. [20] After that, the samples were slowly cooled down to room temperature while under applied pressure. When DCP is added prior to melt pressing, cross-linking occurs that causes the transformation of LDPE into XLPE.…”
Section: Sample Preparationmentioning
confidence: 99%
“…It was found that a soaking period of at least 24 hr was needed to ensure the presence of DCP throughout the pellets (see Supplemental Figure 2). The soaked LDPE pellets were placed between two Teflon sheets and compressed at 17.24 MPa (2,500 psi) at 180 C for 12 min, within the typical cross-linking temperature range of 160-220 C. [20] After that, the samples were slowly cooled down to room temperature while under applied pressure. When DCP is added prior to melt pressing, cross-linking occurs that causes the transformation of LDPE into XLPE.…”
Section: Sample Preparationmentioning
confidence: 99%
“…As known, depending on the applied voltage, it is possible to define three cable groups: low-voltage (LV), medium-voltage (MV) and high-voltage (HV) cables. In the recent decades, the possibility to deliver energy through HVDC links has deepen the Research on innovative insulating materials, aiming at reducing the material DC conductivity and space charge accumulation [1][2]. It has been found that highly pure polymeric compounds are needed in order to ensure acceptable reliability of the final cable system, since impurities i.e., byproducts, volatiles, contaminants and some additives, can act as trapping centers of accumulated charges, which cause significant electric field distortions [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, a lot of research has been focusing on the study of space charge accumulation inside materials for HV applications, primarily through pulsed electroacoustic (PEA) and thermal-step methods [2][3][4][5]. On the contrary, few works focus on the space charge behavior on LV cable systems, mainly due to the fact that the low applied voltage cannot lead to space charge-related insulation failures (as it occurs in the case of HV systems).…”
Section: Introductionmentioning
confidence: 99%
“…High voltage direct current (HVDC) cable, which was first used in 1882 (Krueger, 1995;Mazzanti and Marzinotto, 2013), is an important part in the electric power transmission and distribution system. It is becoming increasingly attractive in electric power transmission and distribution, especially in the open sea or in metropolitan areas due to its much less visual and environmental impact (Krueger, 1995;Mazzanti and Marzinotto, 2013;Zha et al, 2016;Fazal et al, 2016). The HVDC cable is the best choice and a flexibly technical solution in long-distance sea-crossing power transmission lines in transmitting offshore power to the mainland, which helps to reduce traditional fuel consumption, limits the greenhouse gas emission and enhances the use of renewable energy.…”
Section: Introductionmentioning
confidence: 99%